TINJAUAN GEOGRAFIS TERHADAP UPAYA PENGEMBANGAN KAWASAN OBJEK WISATA SARASAH DONAT LEMBAH HARAU DI KECAMATAN HARAU KABUPATEN LIMA PULUH KOTA - Rivan Setiawan; risky ramadhan (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
This study aims to analyze the geographical characteristics and development strategies of the Sarasah Donat tourist attraction in Harau Valley, Lima Puluh Kota Regency. Using a qualitative descriptive method, data were collected through observation, interviews, and documentation. The results show that Sarasah Donat has unique tourism potential, including a donut-shaped waterfall, biodiversity, and natural landscapes. These characteristics are supported by physical conditions such as granite cliffs, fertile andosol soil, and a tropical wet climate. However, challenges such as limited accessibility affect the number of visitors. Development strategies include infrastructure improvement, community empowerment in tourism management, and digital promotion to attract more visitors. Environmental conservation education is also a key focus. The study concludes that sustainable development can enhance the appeal of Sarasah Donat while preserving the natural environment and supporting the well-being of the surrounding community. Keywords: Sarasah Donat; Tourist Attraction; Geographical Study